Analysis of Factors Affecting Company's Financial Performance in the Covid-19 Pandemi (Case Study at PT. Sinar Karya Mustika Manado) - Jeyfenshi Nayoan; Jessy D. L Warongan (Dinasti Publisher, 2022)
To measure the company's financial performance can be seen from two sides, namely from the internal and external sides of the company. Financial performance helps companies to evaluate the company's strengths, weaknesses, and make financial decisions. Good financial performance shows the company can work effectively and efficiently. One of the factors that can show how good the company is or not is by analyzing financial performance. This study aims to analyze what factors influence financial performance during the Covid-19 pandemic. The research method used is qualitative with a case study approach. The results of the study show that the company's financial performance during the Covid-19 pandemic has decreased, because from the results of a review of financial statements, the company has suffered substantial losses in the last two years, namely 2020 and 2021. Then the factors that affect the company's financial performance are: (1). External Factors. Firstly, Government Regulations, namely Large-Scale Social Restrictions and a ban on the export of nickel ore, which then creates other external factors, namely Demand where the prohibition makes the Client Project reduce the number of production requests and the company has to reduce the amount of production, which means that the company's income decreases. Then the last factor is that company financial institutions do not get additional capital that can sustain operations in the midst of a pandemic. (2). Internal factors. First, human resources, where at the time of the pandemic the company reduced employees due to a lack of ability to maintain a number of employees. Of course, the reduction in human resources greatly affected the company's productivity. Second, namely finance, decreased income due to reduced production affects the company's financial performance.